Torbangun (Plectranthus amboinicus (Lour.) Spreng) Leaf Extract Upregulates Expression of Lactation-Related Genes in Human Mammary Epithelial Cells MCF-12A - Tafzi, Fitry; Andarwulan, Nuri; Giriwono, Puspo Edi; Dewi, Fitriya N. (Indonesian Food Science and Technology Journal, 2024)
Torbangun (Plectranthus amboinicus (Lour). Spreng) leaf is a herbaceous plant capable of increasing breast milk, although the mechanism of bioactive compounds on the molecular level remains relatively unknown. Therefore, this study aimed to evaluate the effect of torbangun leaf extract on the expression of genes associated with alveologenesis and the formation of milk protein, namely prolactin receptor (PRLR), glucocorticoid receptor (GR), signal transducer, as well as activator of transcription 5A (STAT5A) and b-casein (CSN2). The result showed that the extract and fractions of torbangunleaf had IC50 values above 20 ug/ml against MCF-12A cells. Ethyl acetate fraction also enhanced the expression of gene GR, STAT5A, and CSN2. Water fraction of torbangun leaf enhanced expression of gene PRLR, GR, STAT5A, and CSN2. The bioactive compound was found to increase the expression of genes associated with proliferation, alveologenesis, and the formation of milk protein during gestation and lactation.